Evaluation and characterization of tuberculosis serodiagnostic biomarkers - Sartain, Mark Jonathan, author; Belisle, John T., advisor; Curthoys, Norman P., committee member; Reardon, Kenneth F., committee member; Schweizer, Herbert P., committee member; Slayden, Richard A., committee member (Colorado State University. Libraries, 2007)
Detection of the antibody response has the potential to provide early and sensitive diagnosis of infection and disease, a critical element of tuberculosis control. The objective of this study was to discover and evaluate Mycobacterium tuberculosis antigens with protein microarray technology. Techniques were established for separation of native M. tuberculosis cytosol and culture filtrate proteins, resulting in 960 protein fractions that were used to generate protein microarrays. Evaluation of serological reactivity from 42 patients in three tuberculosis disease states and healthy purified-protein-derivative positive individuals demonstrated distinct reactivity profiles. Identification of antigens within the reactive fractions yielded eleven products recognized by both cavitary and noncavitary TB patients, and four proteins (HspX, MPT64, PstS1, and TrxC) specific to cavitary tuberculosis patients. Moreover, this approach identified four novel B cell antigens (BfrB, LppZ, SodC, and TrxC) of human tuberculosis, and the seroreactivity of these antigens was validated with more conventional techniques. SodC is one of two superoxide dismutases produced by M. tuberculosis and was previously shown to contribute to virulence. SodC is also a putative lipoprotein and like other sec-translocated mycobacterial proteins it was suggested to be modified with glycosyl residues. The objective of this study was to define the sites and extent of SodC glycosylation. An approach was developed that combined site-directed mutagenesis, lectin binding, and mass spectrometry. Six O-glycosylated residues within a 13 amino acid region were identified near the N-terminus. Each residue was modified with one to three hexosyl units, and the most dominant SodC glycoform was modified with nine hexosyl units. In addition to O-glycosylation of threonine residues, this study provides the first evidence of serine O-glycosylation in mycobacteria. When combined with bioinformatic analyses, the clustering of Oglycosylation appeared to occur in a region of SodC with a disordered structure and not in regions important to the enzymatic activity of SodC. The use of recombinant amino acid substitutions to alter glycosylation sites provided further evidence that glycosylation influences proteolytic processing and ultimately positioning of cell wall proteins.
Keywords: molecular biology; microbiology; biochemistry